1999
DOI: 10.1038/sj.bjc.6690559
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavones inhibit intestinal epithelial cell proliferation and induce apoptosis in vitro

Abstract: The incidence of intestinal cancer is high in Western populations but is relatively uncommon in Asia and Africa (Boyle et al, 1985). It is thought that this variation in incidence is strongly influenced by diet (Armstrong and Doll, 1975;Adlercreutz, 1990) and it is estimated that about 32% of deaths by all cancers, and 70% of deaths from colorectal cancer, could be prevented by a change in diet (Willet, 1995). There is also evidence to suggest that a high intake of soya-based foods (as in populations of Southe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Although the Japanese, who have a high risk of stomach cancer, consume higher amounts of soy foods, an inverse ecological correlation was reported between soy isoflavone intake and stomach cancer deaths in 47 Japanese prefectures . Soy foods are a good source of isoflavones, which have been reported to have antioxidative and anticancer properties . Thus, it is possible that soy has a preventive effect against stomach cancer.…”
mentioning
confidence: 99%
“…Although the Japanese, who have a high risk of stomach cancer, consume higher amounts of soy foods, an inverse ecological correlation was reported between soy isoflavone intake and stomach cancer deaths in 47 Japanese prefectures . Soy foods are a good source of isoflavones, which have been reported to have antioxidative and anticancer properties . Thus, it is possible that soy has a preventive effect against stomach cancer.…”
mentioning
confidence: 99%
“…These findings imply that liquiritin is a good indicator of fermentation, as it is converted to liquiritigenin by Lactobacillus species. The intestinal absorption of aglycone forms is faster and greater than their glycosidic equivalents in vivo, thereby increasing bioavailability and therapeutic efficiency 33, 34, 35, 36. By contrast, the concentrations of hesperidin and 6-gingerol in YJ samples were lower after fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…3-Heteroarylchromones are derivatives of isoflavone, with the chromen-4-one as the core structure, and exhibit some remarkably diverse biological properties, such as antioxidant [6,7], antitumor [8,9], anti-cataract [10], anti-inflammatory, and antifertility [11,12]. In 1989, Ogawara et al [13] reported the inhibitory effect of thiazole isoflavone on tyrosine protein kinase activity.…”
Section: Introductionmentioning
confidence: 98%